Students’ Perception on Learning Vocabulary through WhatsApp Group Media During Covid-19 Pandemic - Tyas Aina Yuskandini; Yuna Tresna Wahyuna; Sumarta Sumarta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
Social networking apps have emerged as potentially useful new tools for improving second language vocabulary acquisition. The current research compares the growth of academic vocabulary knowledge in English. The purpose of this study is to compare the perspectives or views of the Department of English Education at Singaperbangsa Karawang University (UNSIKA). Online learning conducted during the Covid-19 Pandemic students using WhatsApp group media to traditional vocabulary instruction methods. The qualitative research method used in this study is a descriptive design with an explanation of the form of narrative related to the views of students in online learning during the pandemic. Data was collected through interviews specially semi structure interview based on interview guideline and data analysis by involving three students in the online learning process. The findings provide information about the learning process as well as the advantages and disadvantages of WhatsApp media. The interview results show that students in general have a positive attitude toward learning vocabulary through WhatsApp group media. However, technological limitations, unfamiliar presentation, and learning activities may prevent students from participating in a WhatsApp media lesson.